The Utilization of Sweet Potatoes as Prebiotics on The Performance of Lactobacillus sp. in The Vanamei Shrimp Digestion (Litopenaeus vannamei) - Theresia, Maria; Aslamyah, Siti; Sriwulan, Sriwulan (Torani Journal of Fisheries and Marine Science, 2019)
The use of probiotics (Lactobacillus  sp.) in feed is one alternative that is done to improve immunostimulants, growth stimulants, and can be used as a balance of microorganisms in digestion. This study aimed to evaluate the growth performance of vanamei shrimp fed with the addition of Lactobacillus  sp. with sweet potatoes in feed. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment was by feeding with different sweet potato concentrations: A) The dose of sweet potato in feed was 0% (as control); B) The dose of sweet potato in feed was 10%; C) 1The dose of sweet potato in feed was 15%; and D) The dose of sweet potato in feed was 20%. Data were analyzed using variance analysis (ANOVA) and continued with W-Tuckey's further test. The research parameters were digestive enzyme activity, nutrient digestibility, and growth. The results of the variance analysis showed the addition of various sweet potato concentrations with Lactobacillus sp. has no significant effect (p> 0.05) of the growth rate. The specific growth rate of vannamei shrimp ranges from 3.06 to 3.23% / day. Based on the results of the analysis on the utilization of sweet potatoes as a prebiotic on the performance of Lactobacillus sp. in the vannamei shrimps (Litopenaeus vannamei) digestive tract can be concluded that the growth performance does not have a significant effect after being fed with the addition of Lactobacillus sp. and sweet potatoes in feed. Keywords: Enzymes, Digestion, Growth, Lactobacillus sp., Prebiotic, Probiotic.